Determinan Kinerja Individual Di PT. PLN (Persero) Kota Mataram - Chelsha Viba Alief Vanti; Nurabiah Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2026)
Individual performance is one of the key factors in determining the success of an organization, especially in companies engaged in public services such as PT. PLN (PERSERO) in Mataram City. In the era of digitalization and increasingly complex work demands, various factors such as work stress, workload, effectiveness of accounting information systems (AIS), and the use of information are thought to affect the level of employee performance. This study aims to analyze the effect of work stress, workload, effectiveness of accounting information systems, and the use of information technology on individual performance. The study used a quantitative approach with a survey method by distributing questionnaires to employees, and analyze using the probability sampling method and the total of respondents are 122. The result showed that the effectiveness of accounting information systems and the use of information technology significantly influenced individual performance, while work stress and workload did not significantly influence individual performance. These findings indicate that system and technology optimization are important factors in improving employee performance, while the level of stress and workload are still within manageable limits. This study is expected to be a basis for management considerations in improving performance quality through system strengthening and effective use of technology.